PENGUATAN KARAKTER PESERTA DIDIK MELALUI PENGEMBANGAN KURIKULUM BERBASIS REKONSTRUKSI SOSIAL - miranda utari; Sutarto; Muhammad Idris; Yesa Satriya Dwi Hardiyanti (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This study describes strengthening student character education, character education is very important to be instilled in students and must be strengthened with various patterns and strategies that can be carried out, schools as education stakeholders must certainly face problems as challenges in efforts to shape character and it is hoped that in the future Become a better environmental change agent. This study used a qualitative descriptive research methodology with data collection techniques, observation, interviews, with all school members including the al-Ishlah foundation, and supported by literature relevant to the research. The results of the research are reduced and presented, then analyzed to obtain conclusions. The results of the study show that the school's efforts to shape the character of students use various methods, namely the habituation method, exemplary methods and special programs that are carried out in schools in an effort to shape the character of students, which will later be beneficial in society. The form of education applied by the school in strengthening the character values of students is to strengthen adab material.